The mapping of spanish social psychology through its conferences: a bibliometric perspective - Íñiguez-rueda, Lupicinio; Martínez-martínez, Luz María; Muñoz-justicia, Juan Manuel; Peñaranda-cólera, Mª Carmen; Sahagún-padilla, Miguel Angel; Alvarado, José Gerardo (The Spanish Journal of Psychology, 2008)
This study of papers gathered from the proceedings presented at Spanish social psychology conferences explores the use of bibliometrics for studying scientific disciplines. A reference database of all the papers included in the conference proceedings of events held from 1983 to 2000 was generated and classified by thematic area, paper type and author institutional affiliation. The references were laid out on contingency tables and mapped with correspondence analysis. The results show that there is a growing number of co-authored papers and a predominance of empirical over theoretical paper types. Some institutions have a higher concentration of theoretical papers while others work mostly in the areas of organizational and health psychology. In terms of empirical papers, there is a tendency towards generating more qualitative-based studies over the span of time captured by this work. There are also a number of papers written about such areas as cultural psychology that points to the emergence of an interest in critical social psychology. Concluding remarks underline the role of conferences and scientific meetings as an important indicator of the dynamic development of a scientific discipline.